PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PDAM KABUPATEN KUDUS - Novi Permata Sari; Apriatni Endang Apriatni; Handoyo Djoko Waluyo (Jurnal Ilmu Administrasi Bisnis, 2014)
The purpose of this study was to determine the effect of organizational culture variables and physical work environment on employee performance PDAM Kabupaten Kudus . This type of research is explanatory research . In the study population there were 109 permanent employees and all PDAM Kabupaten Kudus were sampled by means of sampling or census saturated . Data were collected through questionnaires . Measurement scale using a Likertscale . Data analysis method used is correlation , simple and multiple linear regression with SPSS 20.0The study concluded that : ( a) organizational culture at PDAM Kabupaten Kudus strong ,as well as the physical work environment on PDAM Kabupaten Kudus Well ; ( b ) The effect of organizational culture on employee performance is strong at 0.805 ; influence of the physical work environment on employee performance is strong at 0.857 (d ) The results stimulatory or jointly demonstrate the organization's culture and physical work environment has a strong influence of 0.895 . Physical work environment variables have a greater influence than the culture of the organization.